ANALISIS PENGARUH INFLASI, KURS RUPIAH/USS DAN SUKU BUNGA SBI TERHADAP HARGA SAHAM PERUSAHAAN SEMEN DI BURSA EFEK INDONESIA - , Deni, S.E ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The objective of this study is to analyze influence of the impact of inflation, exchange rate Rupiah/US$ and SBI interest rate variable toward stock prices. The population of this study is cement listed companies in Indonesia Stock Exchange. Analysis method used is multiple regression. Based on that multiple regression analysis shows that significant influence of inflation, exchange rate Rupiah/US$ and SBI interest rate toward stock prices. The hypothesis of this study is inflation, exchange rate Rupiah/US$ and SBI interest rate was partially and simultaneously affect toward stock price. The results of the partial hypothesis test (t test) showed that the variable inflation had not significant influence toward stock prices on cement companies, however the exchange rate Rupiah/US$ variable had indicate to influence toward stock Prices of PT. Indocement Tunggal Perkasa Tbk and PT. Holcim Indonesia Tbk but not to PT. Semen Gersik (persero), and while the SBI interest rate variable had a significant influence toward stock prices. And the result of this study indicate that simultaneosusly (F test) consisting inflation, exchange rate Rupiah/US$ and SBI interest rate had significant influence toward stock prices of cement companies.